#TITLE_ALTERNATIVE# - Nahar (NIM 280 96 003), Julita
Abstract : The cost of transportation operation is cost that economically occur with operated one transportation in normal condition for a fixed purpose. For transportation service firm, cost is an expense economically sacrificed for the production of service, as in the cost the measurement for the level of service. Cost imposition and consideration must be objective and accurate so that it could be used as basis in the decision making. Cost is of city bus transportation could be classified as operating cost, depreciation cost and overhead cost . Using simple linear regression, each of the cost classified could further be classified into fixed cost and variable cost.The result of test linearity corelation buses Cibiru-Kebon Kelapa at 1998 and 1999 (for quaterly, I, II, III) with travel distance resulted fixed cost Rp 648 per km, varible cost Rp 850 per km so that totally cost bus per km is Rp 1449 on the average level production per month as 55.961 km. From the Break-Even Point (BEP) analysis, found the BEP for buses Cibiru-Kebon Kelapa as 60.580 km per month or Rp 87.780.420 per month, being correlated with average rate at 1998 and 1999 (for quaterly, I, II, III) as Rp 314 per passenger or Rp. 1449 per km, the BEP could not had been passed. The transportation service firm had been gotten financial loss as Rp 2.798.050 per month. Further, being expected the firm could be raised service quality. For that, it may be needed policy for the addition bus minimum bus ready operation per monthly as 13 bus. The raises of rate per month as 4154 rit so that the output average load factor as 98,13%.